2020
DOI: 10.1177/0021998320902510
|View full text |Cite
|
Sign up to set email alerts
|

Open hole tensile testing of 3D printed continuous carbon fiber reinforced composites

Abstract: In this study, the effects of stress concentration on the tensile properties of a 3D printed carbon fiber-nylon composite were investigated. The samples were 3D printed with continuous carbon fiber and chopped fiber reinforced nylon. Samples were manufactured with four different open hole sizes as 3. 175 mm (⅛ in), 6.35 mm (¼ in), 9.25 mm (⅜ in), and 12.7 mm (½ in). Five samples were manufactured for each hole size group. Continuous carbon fibers were printed in the longitudinal direction. Additional reinforce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…The attraction towards the natural fibres such as flax, jute, basalt, bamboo and hemp are also increasing due to their eco friendliness and sustainability [ 137 , 138 , 139 , 140 , 141 , 142 ]. Most of the experiments have been performed with carbon fibre (CF) due to its excellent mechanical properties, lower density, corrosion, wear and moisture resistance, good thermal conductivity and electrical properties, low thermal expansion and piezoresistive behaviour, which is a special feature inherited from CF [ 143 , 144 , 145 , 146 , 147 , 148 ]. Hence, composites printed using CF as the reinforcement with matrix materials such as PEEK, PC, PE and PA are widely used in developing industrial applications, especially in the aerospace and automotive industries [ 149 ].…”
Section: Fibre-reinforced Composite Printingmentioning
confidence: 99%
See 1 more Smart Citation
“…The attraction towards the natural fibres such as flax, jute, basalt, bamboo and hemp are also increasing due to their eco friendliness and sustainability [ 137 , 138 , 139 , 140 , 141 , 142 ]. Most of the experiments have been performed with carbon fibre (CF) due to its excellent mechanical properties, lower density, corrosion, wear and moisture resistance, good thermal conductivity and electrical properties, low thermal expansion and piezoresistive behaviour, which is a special feature inherited from CF [ 143 , 144 , 145 , 146 , 147 , 148 ]. Hence, composites printed using CF as the reinforcement with matrix materials such as PEEK, PC, PE and PA are widely used in developing industrial applications, especially in the aerospace and automotive industries [ 149 ].…”
Section: Fibre-reinforced Composite Printingmentioning
confidence: 99%
“… ( a ) Short CF immersed in Nylon matrix (onyx filament) [ 148 ]. ( b ) The orientation of the printed tensile specimens [ 152 ].…”
Section: Figurementioning
confidence: 99%
“…(a) Analyzing the impact of process parameters on the mechanical behavior of specimens to optimize a certain property or group of properties [4][5][6][7][8][9]; (b) Analyzing the modes of failure to better understand the microstructural failure mechanisms of 3D printed fiber reinforced specimens [1,10,11]; The review is organized as follows. The following part of this section discusses the 3DP process of fiber reinforced composites based on a classification according to the type of fiber, matrix, 3D printer and process specifications.…”
Section: D Printing Fiber Reinforced Polymer Compositesmentioning
confidence: 99%
“…8,13,[16][17][18][19] Flexibility of 3D printing allows to direct the fiber in the desired direction to optimize the mechanical properties of interest. 20,21 Sanei et al 21 printed continuous carbon fiber around the periphery of open hole specimen to mitigate the effect of stress concentration. They observed that failure progression into the hole was blocked by the concentric fibers around the open hole.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Sanei et al. 21 printed continuous carbon fiber around the periphery of open hole specimen to mitigate the effect of stress concentration. They observed that failure progression into the hole was blocked by the concentric fibers around the open hole.…”
Section: Introductionmentioning
confidence: 99%